An examining factors influencing international export and import relationships in context of Vietnam’s free trade agreements - Ha, Le Thi Thanh; Wong, Wing-Keung; Hariyadi, Eko (Universitas Muhammadiyah Yogyakarta, 2024)
Vietnam's trade balance was positive with the United States, the Netherlands, Hong Kong, the United Kingdom, the United Arab Emirates, and Austria. However, it was negative in several countries, including South Korea, China, Taiwan, Thailand, Singapore, and Argentina. This paper aims to investigate the asymmetric effects of several macroeconomic factors on Vietnam's trade balance in the post-global financial crisis era. This paper aims to capture better the nuanced effects of free trade agreements on Vietnam's trade balance. Using regression methods like Pooled OLS, Random Effect Model, Fixed Effect Model, and Hausman Taylor, it analyzes factors affecting bilateral trade with Comprehensive Economic Partnership for East Asia nations. These factors include gross domestic product (GDP), population, distance, exchange rates, national borders, and Free Trade Agreements. Findings suggest that GDP, population, and exchange rates significantly influence Vietnam's trade relationships, but free trade agreements have not yielded the expected results. This study's novelty lies in its exploration of comprehensive regression analysis, offering valuable insights into Vietnam's trade dynamics.